ETOS KERJA TOKOH DALAM NOVEL RANTAU 1 MUARA KARYA A. FUADI - S, Ririn Deviyanti; Syafrial, Syafrial; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to identify the work ethic of characters in novel Rantau 1 Muara By A. Fuadi. Novel Rantau 1 Muara By A. Fuadi tells a lot about the ethos of the work done by figures, so according the author that needs to be researched. Problems in this research is about the work ethic aspect that is divided three, namely: (1) aspect of interpersonal skill shown by 17 characters, (2) aspect of inisiative shown by 16 characters, and (3) aspect of reliable shown by 7 characters. The reference theory is advanced by Hill and Gregory. The type of reasearch is qualitative with analysis descriptive method. Based on research result, the researcher found that 186 datas, thats: (1) 87 datas on interpersonal skill of aspect, (2) 74 datas on inisiative of aspek, and (3) 25 datas on reliable of aspect. So, the most data is on interpersonal skill of aspect and more specially is on help of character . A trait would help ease the burden of others. Based on research can be concluded that the characters in novel Rantau 1 Muara by A. Fuadi has characters that show work ethic. Researcher suggest research about work ethic need to be developed further, becaused of the work ethic in the novel can serve as a role model.Key Word : work ethic, novel, characters